The features of ARVD etiological structure in different age and professional population groups in Saint-Petersburg during 2013–2014 epidemic season - N. I. Lvov; M. M. Pisareva; O. V. Maltsev; J. V. Buzitskaya; V. S. Afanasieva; M. A. Mikhailova; A. Go; M. A. Yanina; N. A. Reznichenko; M. P. Grudinin; K. V. Zhdanov; Yu. V. Lobzin (Журнал инфектологии, 2014)
The objective. To study etiological structure of acute respiratory viral diseases in the hospitalized patients of different age groups and to reveal their peculiarities in children and adults, as well as in adults of draft age (18–26 years) among civilians and military recruits.Materials and methods. 2202 in patients with acute respiratory diseases of moderate and severe degree, including 1123 patients (51.0%) aged up to 18 years and 1079 patients (49,0%) aged 18 years and above, were examined during the epidemic season since September 2013 till July 2014. RNA or DNA of influenza A(H1N1)pdm09 and A(H3N2), influenza B, types 1–4parainfluenza, adenoviruses, respiratory syncytial virus, rino-, metapneumo-, corona-, entero- and boca- viruses were determinedin nasopharyngeal swabs, sputum and brohchoalveolar lavage by real time PCR method. Significance of differences (p<0,05) in cases incidence of compared independent groups were assessed by the Pearson,s χ2 (chi-squared) test.Results. Genetic material of viruses causing ARD was revealed in 1343 cases (61,0%). Influenza viruses A and B (30,3%), RS viruses (23,6%), rinoviruses (22,8%) and adenoviruses (12,5%) prevail among ARD viral pathogens. The parainfluenza virus infection was laboratory confirmed in 8,7%, coronavirus – in 4,4%, bocavirus – in 1,2%, enterovirus – in 0,7% of cases. Assessment of age-related features of ARD etiologic structure showed that RS virus (37,6%, p<0,05) and parainfluenza virus (11,3%, p<0,05) infections were registered significantly often among children. Influenza viruses (46,4%, p<0,05), adenovirus (26,3%, p<0,05) and rinovirus (25,7%, p<0,05) were verified significantly often among adults. Etiologic ARD structure of military personnel 18–26 years old was characterized by significant prevalence of adenovirus infection (53,9%, p<0,05).Conclusion. The study has shown that acute respiratory diseases caused by RS and parainfluenza viruses predominated among children, by influenza viruses – among adults (civilians) and by adenovirus – among military personnel.